2016
DOI: 10.1002/mrm.26395
|View full text |Cite
|
Sign up to set email alerts
|

Motion-robust cardiac B1+ mapping at 3T using interleaved bloch-siegert shifts

Abstract: Purpose To develop and evaluate a robust motion-insensitive Bloch-Siegert shift based B1+ mapping method in the heart. Methods Cardiac Bloch-Siegert B1+ mapping was performed with interleaved positive and negative off-resonance shifts and diastolic spoiled gradient echo imaging in twelve heartbeats. Numerical simulations were performed to study the impact of respiratory motion. The method was compared to 3D actual flip angle imaging (AFI) and 2D saturated double angle method (SDAM) in phantom scans. Cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 72 publications
2
18
1
Order By: Relevance
“…The greater robustness of the interleaved acquisition scheme has led to its adoption in more recent work using this technique. 11,26 In the interleaved case, however, our numerical simulations showed that the phase never reached steady-state but rather a pseudo-steady-state that alternated between two conditions depending on the frequency of the preceding offresonance BS pulse. As a result, the difference in phase between interleaves is not solely due to the BSS effect and, therefore, does not match the phase difference of the sequential ordering scheme (Figure 2).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The greater robustness of the interleaved acquisition scheme has led to its adoption in more recent work using this technique. 11,26 In the interleaved case, however, our numerical simulations showed that the phase never reached steady-state but rather a pseudo-steady-state that alternated between two conditions depending on the frequency of the preceding offresonance BS pulse. As a result, the difference in phase between interleaves is not solely due to the BSS effect and, therefore, does not match the phase difference of the sequential ordering scheme (Figure 2).…”
Section: Discussionmentioning
confidence: 81%
“…The resulting B1+ maps had visible artefacts and large biases (see Figure , right column). The greater robustness of the interleaved acquisition scheme has led to its adoption in more recent work using this technique …”
Section: Discussionmentioning
confidence: 99%
“…The resulting B1 + maps had visible artefacts and large biases (Fig.8, right column). The greater robustness of the interleaved acquisition scheme has led to its adoption in more recent work using this technique 9,24 .…”
Section: Discussionmentioning
confidence: 99%
“…For the second set of experiments, the manufacturer's GRE sequence was modified for BSS B1+ mapping by adding a Fermi‐shaped off‐resonance RF pulse (frequency shift: ±4 kHz; duration: 8 ms; nominal B 1 + ‐peak: 5.5 μT (the maximum allowed due to SAR limits)). Positive and negative images were acquired in an interleaved fashion 30,35–38 (Figure 1A). To reduce the effects of on‐resonance excitation, the off‐resonance RF pulse was surrounded by bipolar crusher gradient lobes in the slice‐selection direction that provides 4π phase difference within a voxel 33 (Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, BSS B1+ mapping works for a relatively large dynamic range of B1+, and it is insensitive to T 1 relaxation and magnetization transfer effects 27 . With these promising features, BSS B1+ mapping has attracted considerable attention since its discovery supported by numerous studies 28–38 …”
Section: Introductionmentioning
confidence: 99%